2022
DOI: 10.1002/glia.24309
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation accelerates Wallerian degeneration and promotes nerve regeneration after sciatic nerve injury

Abstract: Following peripheral nerve injury (PNI), Wallerian degeneration (WD) in the distal stump can generate a microenvironment favorable for nerve regeneration. Brief low‐frequency electrical stimulation (ES) is an effective treatment for PNI, but the mechanism underlying its effect on WD remains unclear. Therefore, we hypothesized that ES could enhance nerve regeneration by accelerating WD. To verify this hypothesis, we used a rat model of sciatic nerve transection and provided ES at the distal stump of the injured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 77 publications
2
14
0
1
Order By: Relevance
“…Wallerian degeneration in the injured nerve plays a vital role in creating favorable microenvironment for nerve regeneration (Li et al, 2022). It is well known that both macrophages and Schwann cells can engulf the axonal and myelin debris.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallerian degeneration in the injured nerve plays a vital role in creating favorable microenvironment for nerve regeneration (Li et al, 2022). It is well known that both macrophages and Schwann cells can engulf the axonal and myelin debris.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, RhoA plays roles in Schwann cells differentiation through the JNK pathway, while affecting Schwann cells proliferation by regulating the AKT pathway (Tan et al, 2018; Wen et al, 2018; Wen, Qian, et al, 2017). After nerve injury, Schwann cells dedifferentiate and transform into the repair phenotype, which can clear the debris of axons and myelin to accelerate Wallerian degeneration, and secrete neurotrophins to enhance nerve regeneration (Jessen & Mirsky, 2016; Klimovich et al, 2021; Li et al, 2022). Until now, the role of RhoA in Schwann cells for nerve injury and regeneration has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“… Neuromodulation and noninvasive electrical stimulation: the cluster analysis of literature co-citations and literature co-citations in the last 5 years shows that neuromodulation and noninvasive electrical stimulation are continuing hotspots in this field. Neuroelectrical stimulation is a noninvasive stimulation strategy ( 32 ) that transforms neuronal networks from dormant to functional, thereby gradually restoring control over paralyzed muscles ( 33 , 34 ). In this regard, “numerical models” enhanced by deep learning algorithms are the basis for theoretical simulations of neurostimulation techniques and provide technical guidance for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reported optimal parameters for ES are an intensity of 100 mV/mm ES and a duration of 1 h ( Hu et al, 2019 ). Concerning SC stimulation, Koppes et al found that electrically stimulating SCs at a frequency of 20 Hz (with pulses of 100 μs at 3 V) in an electrotaxis setup led to the overexpression of growth-associated protein (GAP)-43, ɑ1-tubulin, and TrkB, all of which contribute to axonal outgrowth and nerve regeneration ( English et al, 2007 ; Geremia et al, 2007 ; Koppes et al, 2014 ; Li et al, 2023 ).…”
Section: Electrical Stimulation In Peripheral Nerve Regenerationmentioning
confidence: 99%